Disrupting Finance FinTech and Strategy in the 21st Century - Lynn, Theo.; Mooney, John G.; Rosati, Pierangelo; Cummins, Mark.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Palgrave Pivot, 2019)
This open access Pivot demonstrates how a variety of technologies act as innovation catalysts within the banking and financial services sector. Traditional banks and financial services are under increasing competition from global IT companies such as Google, Apple, Amazon and PayPal whilst facing pressure from investors to reduce costs, increase agility and improve customer retention. Technologies such as blockchain, cloud computing, mobile technologies, big data analytics and social media therefore have perhaps more potential in this industry and area of business than any other. This book defines a fintech ecosystem for the 21st century, providing a state-of-the art review of current literature, suggesting avenues for new research and offering perspectives from business, technology and industry.
Deciphering Crowdfunding -- Addressing Information Asymmetries in Online Peer-to-Peer Lending -- Machine Learning and AI for Risk Management -- What Fintech Can Learn from High-Frequency Trading: Economic Consequences, Open Issues and Future of Corporate Disclosure -- InsurTech -- Understanding RegTech for Digital Regulatory Compliance -- Payment Service Directive II and its Implications -- From Transactions to Interactions: Social Considerations for Digital Money -- Token-based Business Models -- Blockchain beyond Cryptocurrencies.
Keywords: Technological innovations; Business information services; Financial services industry; Big data; Innovation and Technology Management; IT in Business; Financial Services; Big Data